PENGEMBANGAN MOVEMENTS AND SONG FOR BASIC SEXUAL EDUCATION (MEBO) UNTUK MENGENALKAN PENDIDIKAN SEKSUAL ANAK USIA DINI - Fifi Amalia Putri; Yes Matheos Lasarus Malaikosa; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a learning media called MEBO (Movements and Song for Basic Sexual Education) to introduce basic sexual education to children aged 5–6 years, focusing on body ownership, personal boundaries, and the ability to reject inappropriate touch. The study employed a Research and Development (R&D) approach using the ADDIE development model. The research subjects consisted of 40 children from four kindergartens in Surabaya: TK Bahrul Ulum, TK Hidayatullah, TK Permata, and TK Bina Tunas Bangsa. Data were collected through expert validation questionnaires, teacher practicality questionnaires, and child observation. Validation results showed that MEBO obtained 86.11% from the content expert and 87.5% from the media expert, both in the very feasible category. Practicality tests across four institutions yielded scores between 82.14%–100%, classified as very practical. Effectiveness testing using One-Way ANOVA showed a significance value of 0.047 (p < 0.05), indicating a significant difference between groups after using MEBO. Therefore, MEBO is declared valid, practical, and effective as an early childhood sexual education learning media.